A hybrid mass damper system controlled by H control theory for reducing bending torsion vibration of an actual building. - Fujinami, Takeyoshi
A pair of hybrid mass dampers has been installed on an actual 23 storey building located in Tokyo. The aim of the dampers is to counteract wind and smaller earthquake excited oscillations. H control theory has been applied to control the dampers for reducing both bending and torsion vibrations simultaneously. For the design of the controller, identification parameters resulting from the forced vibration test of the building are adopted. The target of the controleer performance is to reduce the vibration of first mode and to keep robust stabilization over the second or higher mode. From the results of forced vibration tests conducted after installation of the controller, it was confirmed that this system has proven control effect, largely satisfying what was aimed for in the design. Furthermore, system performance has been continually recorded during earthquakes, and analysis of the data has proved control effect.
Keywords: Hybrid mass damper; H control theory; Bending and torsion vibration; Simultaneous control